An unusual cause of acute lower gastrointestinal bleeding: lung adenocarcinoma metastasis to the descending colon. Issue 8 (20th June 2017) - Papanikolaou, Ioannis S.; Gkolfakis, Paraskevas; Tziatzios, Georgios; Grammatikos, Konstantinos; Panayiotides, Ioannis G.; Tsakiraki, Zoi; Zinovieva, Irina; Dimitriadis, George D.; Triantafyllou, Konstantinos
Key Clinical Message: Lung adenocarcinoma with symptomatic GI metastasis occurs seldom in everyday clinical practice. However, as diagnostic modalities, therapeutic interventions, and supportive care for cancer evolve, it is likely that the clinician might encounter a number of similar cases in the future, and therefore, he should be aware of this rare entity. Abstract : Lung adenocarcinoma with symptomatic GI metastasis occurs seldom in everyday clinical practice. However, as diagnostic modalities, therapeutic interventions, and supportive care for cancer evolve, it is likely that the clinician might encounter a number of similar cases in the future, and therefore, he should be aware of this rare entity.